The Differences of Nutrient Components in Edible and Feeding Coix Seed at Different Developmental Stages Based on a Combined Analysis of Metabolomics - Wei, Xiaoyan; Li, Yong; Zhou, Shufeng; Guo, Chao; Dong, Xiaolong; Li, Qishuang; Guo, Juan; Wang, Yanan; Huang, Luqi (Molecules (Basel, Switzerland), 2023)
Coix lachryma-jobi L. is an excellent plant resource that has a concomitant function for medicine, foodstuff and forage in China. At present, the commonly used cultivar for both medicine and foodstuff is Xiaobaike, and the cultivar for foraging is Daheishan. However, differences in the internal composition of plants lead to the expression of different phenotypic traits. In order to comprehensively elucidate the differences in nutrient composition changes in Coix seeds, a non-targeted metabolomics method based on ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (LC-Q-TOF-MS) was used to analyze the metabolic changes in Coix seeds at different developmental stages. An edible Coix relative (Xiaobaike) and a feeding Coix relative (Daheishan) were selected as the research subjects. In the metabolome analysis of Coix seed, 314 metabolites were identified and detected, among which organic acids, carbohydrates, lipids, nucleotides and flavonoids were the main components. As an important standard for evaluating the quality of Coix seed, seven lipids were detected, among which fatty acids included not only even-chain fatty acids, but also odd-chain fatty acids, which was the first time detecting a variety of odd-chain fatty acids in Coix seed. The analysis of the compound contents in edible and feeding-type Coix lachryma-jobi L. and the lipid content at the mature stage showed that, among them, arachidic acid, behenic acid, heptadecanoic acid, heneicosanoic acid and pristanic acid may be the key compounds affecting the lipid content. In addition, in the whole process of semen coicis maturation, edible and feeding Coix show similar trends, and changes in the third period show clear compounds in the opposite situation, suggesting that edible and feeding Coix not only guarantee the relative stability of species but also provide raw materials for genetic breeding. This study provides valuable information on the formation of the edible and medicinal qualities of Coix.